IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR PKN DI SEKOLAH DASAR - Muhammad Asyar; Dg. Mapata (LPPM Universitas Muhammadiyah Bulukumba, 2023)
This research aims to determine whether there is an increase in PKN learning outcomes through the Student Teams-Achievement Divisions (STAD) cooperative learning model for Class V students at SDN 26 Matekko, Bulukumba district. The problem formulated: whether the Student Teams-Achievement Divisions (STAD) cooperative learning model can improve PKN Class V learning outcomes at SDN 26 Matekko Regency. Bulukumba. This type of research is classroom action research (which is described by qualitative and quantitative analysis to reveal research results in accordance with the data and facts obtained in class. The implementation of this research is through an activity process consisting of four stages, including planning, implementing actions, observing and reflecting. The PTK cycle was shown to be an improvement on the results of reflection on previous actions, and was considered not successful. This problem was attempted to be solved again by following the previous cycle. The results of the action research obtained in cycle I, the percentage of students who asked for guidance from their group friends was 41.67% and increased to 53.21% in cycle II. Then students' self-confidence also increased with students' courage to raise their hands to represent their group to present a percentage of the results of their group's work. It can be seen that in cycle I the percentage was 15.38% and increased to 22.44% in cycle II.